Antibacterial, Antioxidant, and Anticholinesterase Activities of Plant Seed Extracts from Brazilian Semiarid Region. (10th December 2013) - Farias, Davi Felipe; Souza, Terezinha Maria; Viana, Martônio Ponte; Soares, Bruno Marques; Cunha, Arcelina Pacheco; Vasconcelos, Ilka Maria; Ricardo, Nágila Maria Pontes Silva; Ferreira, Paulo Michel Pinheiro; Melo, Vânia Maria Maciel; Carvalho, Ana Fontenele Urano
Abstract : The antimicrobial, antioxidant, and anticholinesterase activities of ethanolic seed extracts of twenty-one plant species from Brazilian semiarid region were investigated. The extracts were tested for antimicrobial activity against six bacteria strains and three yeasts. Six extracts presented activity against the Gram (−) organism Salmonella choleraesuis and the Gram (+) organisms Staphylococcus aureus and Bacillus subtilis . The MIC values ranged from 4.96 to 37.32 mg/mL. The Triplaris gardneriana extract presented activity against the three species, with MIC values 18.8, 13.76, and 11.15 mg/mL, respectively. Five extracts presented antioxidant activity, with EC50 values ranging from 69.73  μ g/mL ( T. gardneriana ) to 487.51  μ g/mL ( Licania rigida ). For the anticholinesterase activity, eleven extracts were capable of inhibiting the enzyme activity. From those, T. gardneriana, Parkia platycephala and Connarus detersus presented the best activities, with inhibition values of 76.7, 71.5, and 91.9%, respectively. The extracts that presented antimicrobial activity were tested for hemolytic assay against human A, B, and O blood types and rabbit blood. From those, only the Myracrodruon urundeuva extract presented activity (about 20% of hemolysis at the lowest tested concentration, 1.9 µg/mL). Infrared spectroscopy of six representative extracts attested the presence of tannins, polyphenols, and flavonoids, which was confirmed by a qualitative phytochemical assay.